The Numerical Study of a Dropwise Condensation Mode when Cooling Heat Transfer Surfaces; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Krainov A. V. Aleksander Valerievich; Pashkov E. N. Evgeny Nikolaevich; Lushnikov R. E.; Arkhipov V. A. (Numerical Simulation of Physical and Chemical Processes, 2016)
Title screen